2023
DOI: 10.1177/08862605221145722
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parental Phubbing and Interpersonal Aggression in Adolescents: The Role of Rejection Sensitivity and School Climate

Abstract: The impact of parental phubbing has attracted the attention of researchers, especially concerning adolescents’ online behavior. However, limited research has studied the influence of parental phubbing on interpersonal aggression, including the underlying mechanism. Grounded in parental acceptance–rejection theory, the present study investigated the association between parental phubbing and interpersonal aggression as well as the mediating role of rejection sensitivity among adolescents. Additionally, school cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The interruption due to cell phone usage is a risk factor of children and adolescents’ development ( McDaniel, 2021 ). Numerous studies found that parental phubbing not only impacts negatively on conversation and relationship quality ( Radesky et al, 2015 ; Kildare and Middlemiss, 2017 ; Niu et al, 2020 ; Liu et al, 2021a ), but also on children’s mental health ( Wang et al, 2020 ; Wei et al, 2021 ; Wang and Qiao, 2022 ; Xiao and Zheng, 2022 ; Ding et al, 2023 ; Mi et al, 2023 ; Zhao et al, 2023 ). However, no research to date has directly focused on the association between parental phubbing and child–parent interaction, such as filial piety behavior which remains one of the goals of parents in educating their children in modern Chinese society.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The interruption due to cell phone usage is a risk factor of children and adolescents’ development ( McDaniel, 2021 ). Numerous studies found that parental phubbing not only impacts negatively on conversation and relationship quality ( Radesky et al, 2015 ; Kildare and Middlemiss, 2017 ; Niu et al, 2020 ; Liu et al, 2021a ), but also on children’s mental health ( Wang et al, 2020 ; Wei et al, 2021 ; Wang and Qiao, 2022 ; Xiao and Zheng, 2022 ; Ding et al, 2023 ; Mi et al, 2023 ; Zhao et al, 2023 ). However, no research to date has directly focused on the association between parental phubbing and child–parent interaction, such as filial piety behavior which remains one of the goals of parents in educating their children in modern Chinese society.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study demonstrated that parental phubbing negatively predicts RFP behavior and does not predict AFP behavior, which is consistent with Hypothesis 1. Many studies have utilized Chinese samples to investigate the consequences of parental phubbing ( Niu et al, 2020 ; Wang et al, 2020 ; Liu et al, 2021a , b ; Wang and Qiao, 2022 ; Xiao and Zheng, 2022 ; Ding et al, 2023 ; Zhao et al, 2023 ). However, these studies primarily focus on the impact of parental phubbing on children’s mental health indicators (such as depression, anxiety, self-esteem, mobile phone addiction, sleep quality, suicidal ideation, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations